OPTIMIZING SUSTAINABLE FURNITURE DESIGN THROUGH THE APPLICATION OF AGRICULTURAL WASTE STRAW: AN OPERATIONAL RESEARCH APPROACH - Yuqing Wang; Siti Suhaily Surip (Operational Research in Engineering Sciences: Theory and Applications, 2024)
This research focuses on sustainable furniture design using agricultural waste straw biomass. That is why it brings out the aspect of sustainable development in design, which encompasses the consideration of ecological quality, waste minimization and management of resources. The paper focuses on composite materials that include straw biomass and discusses major steps including material selection, manufacturing technique, and Life Cycle Assessment (LCA).  The research uses hot pressing, injection moulding and 3D printing techniques to evaluate bio-composite application of straw for furniture to understand its value in minimising the negative effects on the environment and constituents in a circular economy paradigm. This paper uses the Analytic Hierarchy Process (AHP) to assess sustainable design measures and decision-making models, with difficulties such as consistency of quality and customer affectivity. The results indicate that today’s appearance and technological breakthroughs need to be incorporated to enhance the economic feasibility and sustainability of straw. This study serves as a source of applied information and directions on how waste material can be used to address sustainable design of furniture and ultimately, effect change in and improve resource use efficiencies within the furniture industry.